Isolated proximal greater saphenous vein thrombosis and the risk of propagation to deep vein thrombosis and pulmonary embolism - Kim SH; Patel N; Thapar K; Pandurangadu AV; Bahl A (Vascular Health and Risk Management, 2018)
Samuel H Kim,1 Nimesh Patel,2 Kanika Thapar,2 Ananda V Pandurangadu,3 Amit Bahl1 1Department of Emergency Medicine, William Beaumont Hospital, Royal Oak, MI, USA; 2Oakland University William Beaumont School of Medicine, Rochester, MI, USA; 3Department of Emergency Medicine, Rush University, Chicago, IL, USA Objectives: Greater saphenous vein (GSV) thrombosis is concerning due to its close proximity to the deep femoral vein. This study sought to identify the risk of propagation to deep vein thrombosis (DVT) or pulmonary embolism (PE) among patients with isolated proximal GSV superficial thrombosis and describe provider practice patterns related to treatment. Materials and methods: This is an Institutional Review Board-approved retrospective multicenter study. Patients presented to one of three possible emergency departments in a large health system. About 21,716 patients were queried through the electronic medical record. Ninety-five patients or 0.4% of study subjects met inclusion criteria of isolated proximal GSV thrombosis. Forty-five patients were excluded, leaving a final data set of 40 patients. Investigators recorded radiology impressions, patient demographics, past medical history, DVT/PE risk factors, and treatment plans. Propagation of GSV thrombosis to DVT/PE was also noted. Follow-up methods included chart review, primary care physician follow-up, and direct, scripted patient follow-up phone calls. Descriptive statistics were applied to study subjects using SAS for Windows, version 9.3. Results: Three patients (7.5%) had progression of GSV thrombosis to DVT/PE. Twenty percent of patients without malignancy were treated with anticoagulation compared to 14% of those with preexisting malignancy upon initial diagnosis of isolated GSV thrombosis. Forty-five percent of patients were prescribed some type of supportive therapy to aid in the treatment of GSV thrombosis. Conclusion: Isolated proximal GSV thrombosis, while uncommon, may frequently progress to DVT or PE. Our work suggests clinicians should consider anticoagulation for isolated GSV thrombosis. Keywords: greater saphenous vein thrombosis, superficial vein thrombosis, venous thromboembolism